Topografia da resistência digital: espaços de resistência no contexto do trabalho de plataforma digital - Neves, Ianaira Barretto Souza (2024)
Previous research dedicated to the field of digital platforms has extensively investigated the understanding of how algorithmic control is employed for workforce management. However, beyond comprehending the mechanisms of control, it becomes relevant to unveil how algorithmically managed platform workers engage in acts of opposition to this type of control and what spaces of resistance they construct. This study aims to analyze how workers resist algorithmic management in digital platform work based on the resistance narratives of fooddelivery workers in Brazil. To do so, I conducted qualitative and empirical research employing thematic analysis of narratives, based on data collected over three years of research. Data collection involved ethnographic interviews, observations, field insertions, and digital ethnography within a WhatsApp group. From the emerging resistance narratives of the workers, I identified three distinct spaces of resistance: Resistance in physical space, Resistance in hybrid space, and Resistance in imaginative space. These categories demonstrated that contrary to the scenario of absolute control pointed out by some previous studies, workers in digital fooddelivery platforms oppose and resist in different spaces, and these spaces are not mutually exclusive. Thus, the research contributes to theoretical and empirical advancements in studies on organizations and technology, algorithm-mediated management, work on digital platforms, and emerging studies on resistance to digital platform work. Finally, methodologically, it advances debates on the challenges of conducting investigations simultaneously in digital and physical spaces.